STUDI PRINSIP- PRINSIP DESAIN PADA INTERIOR SALON HAIR CREATOR - Waisnawa, I Made Jayadi (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
The growth of beauty salons is now increasing between 10-15 percent. This is supported by the development of a beauty salon which was previously just a lifestyle and now become a business. The growth of beauty salon is not only supported by the service to the consumer, but also must be supported by the interior design. The atmosphere of the room and space is the priority of the owners to attract visitors. Hair Creator became one of the growing beauty salons in Bali. Hair Creator can now be found in five major shopping centers in Bali namely Centro, Lippomall, Beachwalk, Mall Bali Galeria (MBG) and Level 21. Hair salon interior design is visually aesthetic. This is why the interior design of Hair Creator is very interesting to be used as study material in studying the principles of design. The design principles which become the guide of the space preparation are a priority in the interior design of Hair Creator. There are seven principal types of design principles: proportion, scale, balance, harmony, unity, rhythm and emphasis. Colors and alignment are the two principles design that dominate the five hair salon interior designs. Color as the principle of emphasis is presented on furniture furnishing elements. The principle of harmony is presented by combining elements of texture, motifs and colors on the elements of space. In addition, the principle of alignment is also prepared by looking for the characteristics of the design elements.